A Hierarchy of Discrete Integrable Coupling System with Self-Consistent Sources. (27th August 2014) - Li, Yuqing; Dong, Huanhe; Yin, Baoshu
Abstract : Integrable coupling system of a lattice soliton equation hierarchy is deduced. The Hamiltonian structure of the integrable coupling is constructed by using the discrete quadratic-form identity. The Liouville integrability of the integrable coupling is demonstrated. Finally, the discrete integrable coupling system with self-consistent sources is deduced.